2022
DOI: 10.1108/ijchm-09-2021-1117
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory prosumption: how cooking classes shape perceptions of destinations

Abstract: Purpose This study aims to examine the multisensory experiences of participating in a cooking class and how they shape perceptions of destinations in the pre-trip stage. Performance theory and prosumption provide a theoretical lens to investigate how a cooking class influences the pre-trip destination sensescape. Design/methodology/approach This study used participatory action research consisting of an immersive Tatarstan cooking class experience with the supporting materials of music and videos, focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…From a managerial viewpoint, the findings suggest that managers should enhance telepresence and deploy more interactive gamification activities to increase viewers' impulsive consumption during livestreaming sessions. Aksenova et al (2022) investigate the role of cooking classes as a pre-trip marketing tool that can improve the competitiveness of a tourism destination. Through a participatory action research conducted during an immersive cooking class experience complemented by visual and audible representations of the Republic of Tatarstan, the authors observe participants and collect data from focus groups in the UK.…”
Section: Value and Image Of Gastronomy Experiences By Restaurants And...mentioning
confidence: 99%
See 1 more Smart Citation
“…From a managerial viewpoint, the findings suggest that managers should enhance telepresence and deploy more interactive gamification activities to increase viewers' impulsive consumption during livestreaming sessions. Aksenova et al (2022) investigate the role of cooking classes as a pre-trip marketing tool that can improve the competitiveness of a tourism destination. Through a participatory action research conducted during an immersive cooking class experience complemented by visual and audible representations of the Republic of Tatarstan, the authors observe participants and collect data from focus groups in the UK.…”
Section: Value and Image Of Gastronomy Experiences By Restaurants And...mentioning
confidence: 99%
“…Aksenova et al (2022) investigate the role of cooking classes as a pre-trip marketing tool that can improve the competitiveness of a tourism destination. Through a participatory action research conducted during an immersive cooking class experience complemented by visual and audible representations of the Republic of Tatarstan, the authors observe participants and collect data from focus groups in the UK.…”
Section: Contributionsmentioning
confidence: 99%
“…Previous researchers validated authenticity as one of the key business characteristics (Aksenova et al, 2022). It was reported that consumers are affected by inauthenticity associated with consumption (Leigh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although sensory marketing practices are widely applied in the hospitality industry, relevant research findings are surprisingly scarce and scattered in the hospitality literature (Aksenova et al , 2022; Lee et al , 2019). Sensory marketing publications have surged in the marketing and retailing disciplines in the past decade (Biswas, 2019; Krishna, 2012; Labrecque, 2020); however, their implications, though potentially useful, have not been fully discussed in the context of hospitality, and therefore the transfer of knowledge to hospitality operators is limited.…”
Section: Introductionmentioning
confidence: 99%